The EMMA non-scaling FFAG - Edgecock,R; Kelliher,D; Machida,S; Beard,C; Bliss,N; Clarke,J; Griffiths,S; Hill,C; Jamison,S; Jones,J; Kalinin,A; Marinov,K; et al. (2010)
The Electron Model for Many Applications (EMMA) will be the World's first non-scaling FFAG and is under construction at the STFC Daresbury Laboratory in the UK. Construction is due for completion in Summer 2010 and will be followed by commissioning with beam and a detailed experimental programme to study the functioning of this type of accelerator. This paper will give an overview of the motivation for the project and describe the EMMA design and hardware. The first results from commissioning will be presented in a separate paper.